Association between HLA and Guillain Barre’ syndrome - Raouf, Hyam (AL-Kindy College Medical Journal, 2016)
Background: Genetic factors play an important role in susceptibility to Guillain Barre’ syndrome. Human leukocyte antigen (HLA) as part of immune system has a role in the disease process.Aim of the study: to assess the relationship between HLA-A alleles with Guillain Barre’ syndrome (GBS) compared with a healthy control group using PCR-SSOP method.Type of the study: Cross-sectional study.Patients and methods:Patient’s group consisted of 30 Iraqi Arab Muslims patients with Guillain Barre’ syndrome that consulted the Neurological department in Neurosciences Hospital between January-2013 to January- 2014 were genotyped for HLA-A alleles. A control group consisted of 30 healthy volunteers among the staff of AL-Kindi College of Medicine that did not have any neurological disorders.Results: Present study found a decreased frequency of HLA-A:0101 allele (p=0.001) in GBS patients compared to healthy controls.Conclusions: current results suggest that GBS is negatively associated with HLA-A:0101 allele.